PEMANFAATAN DAUN PEPAYA SEBAGAI BAHAN PUPUK ORGANIK CAIR (POC) DI DESA BULU - Indra Puji Astuti; Doni Susanto; Erny Untari (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
This community service activity is in the form of training on the manufacture of Liquid Organic Fertilizer (POC) which was held in Bulu Village, Sukomoro District, Magetan Regency. The background of this activity was carried out because of the presence of many papaya leaves and the lack of utilization of these leaves so that many leaves fell and became garbage. The method used is the presentation of material from the team and then direct practice of making POC from papaya leaves together with residents. After the training is carried out, it is expected to provide insight and skills to the community in making POC. In addition, it is also hoped that the community can take advantage of POC to be given to their own plants.